Federated States of Micronesia : 2010 Article IV Consultation-Staff Report; a Public Information Notice; and a Statement by the Executive Director of the Federated States of Micronesia on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
The economy has recovered following the stabilization of commodity and food prices. The Article IV discussions focused on policies to secure a sustained recovery and achieve long-term economic and fiscal sustainability. The recovery will likely remain weak, and the consolidated fiscal surplus is expected to decline in the near term. Long-term sustainability could be achieved through increasing the fiscal surplus. The reliability, coverage, and timeliness of economic statistics need to be improved to guide policies. The global crisis has increased the urgency of major fiscal and structural reforms.